Design and Application of a Drip Irrigation System Using Solar Power - David P. Rumambi; Ruland A. Rantung; Hildy Wullur (Jurnal Ilmiah Sains, 2025)
This research aims to design and apply a solar-powered drip irrigation system that is efficient in water use, especially on dry land. The system is designed using 100 WP solar panels to drive drip irrigation pumps, thus saving energy and reducing dependence on conventional energy sources. The research was conducted at the Green House of the Faculty of Agriculture, Sam Ratulangi University, with the method of assembling and testing the performance of the system. The results show that this drip irrigation system has a water flow uniformity coefficient of 97% with an average discharge per dripper reaching 24.53 ml/minute. This system allows for consistent water distribution and meets the water needs of pakcoy plants in dry land. The application of this solar-based drip irrigation system not only improves water use efficiency but also offers environmentally friendly and energy-saving solutions. The results of this study support the use of renewable energy in the agricultural sector and are expected to be adapted to various locations with similar geographical conditions to support sustainability and food security. Keywords: Drip irrigation; dryland; renewable energy; solar power; water efficiency